2022
DOI: 10.3390/antiox11071332
|View full text |Cite
|
Sign up to set email alerts
|

Zeolites and Biochar Modulate Olive Fruit and Oil Polyphenolic Profile

Abstract: Soil degradation processes and climate change threaten the sustainability of Mediterranean rainfed olive orchards, with repercussions on crop yield and quality of olives, olive oil and olive by-products. Using soil amendments can enhance soil fertility for sustained environmental quality and plant performance. For two years, we evaluated, under rainfed conditions, the effects of a fertilizer compound (FC) and its combination with zeolites (ZL) and biochar (BC) amendments on soil moisture, yield, fruit and oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Aiming to study the correlation between the various individual phytochemicals and each bioactivity, score-plots similar to those presented in Figure 5 for PCA were obtained using the OPLS-DA (orthogonal partial least squares discriminant analysis) model. This analysis allows an easier interpretation and presents advantages to data sets comprising a higher number of observations than the number of variables, being proposed as a promising tool to highlight statistically significant components in comparable data sets [ 28 , 40 ]. The OPLS-DA model uses an orthogonal signal correction filter to identify the variations related to the prediction of a quantitative response from the variations not related to the prediction [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aiming to study the correlation between the various individual phytochemicals and each bioactivity, score-plots similar to those presented in Figure 5 for PCA were obtained using the OPLS-DA (orthogonal partial least squares discriminant analysis) model. This analysis allows an easier interpretation and presents advantages to data sets comprising a higher number of observations than the number of variables, being proposed as a promising tool to highlight statistically significant components in comparable data sets [ 28 , 40 ]. The OPLS-DA model uses an orthogonal signal correction filter to identify the variations related to the prediction of a quantitative response from the variations not related to the prediction [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Principal component analysis (PCA) was used to evaluate inter-year variance of the individual phenolic components and performed as described by Ferreira, et al 2020 [ 27 ]. The correlation between individual phytochemicals and antioxidant or enzymatic inhibition activities was performed through orthogonal partial least squares-discriminant analysis (OPLS-DA), as described by Martins, et al 2022 [ 28 ]. Statistical analyses and graphic design were performed using Statistica (Version 14; TIBCO Software Inc., California, USA), SIMCA software (Version 14.1.…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, in general, oils from legume cover crops, especially when combined with zeolites, showed lower values of FA, PI, K232, K270 and ∆K. While FA measures the hydrolytic breakdown of triglycerides to di- and monoglycerides, leading to fatty acid release, PI measures the release of peroxide compounds arising from primary oxidation and spectrophotometric values, and K232 and K270 measure conjugated dienes and trienes and their secondary oxidation products [ 59 ]. The highest values obtained in the T olive oils suggests a higher level of hydrolytic breakdown, damage and oxidation, than in the other soil treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Having scarce information about the influence of legume cover crops on the commercial quality indices of olive oils, previous studies have revealed a similar pattern of free acidity response [ 24 , 60 ], while no significant effects of legumes were detected in the peroxide index, K232, K270 or ∆K [ 24 ]. Meanwhile, the application of zeolites increased the oleic/linoleic ratio and ameliorated the oil quality indices FA, PI and K232, when compared with the single use of NPKB fertilizers in a rainfed olive orchard [ 59 ]. On the other hand, in 2019, the free acidity response was reversed, showing that the T olive oil had the lowest value, while for the rest of the evaluated parameters (i.e., primary oxidation (PI, K232), advanced oxidation (K270), hydrolytic alteration (acidity)), no influence of soil management treatment was found.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, olive oil is an important source of heart-healthy fats along with vitamins. It is also associated with several beneficial effects on human health due to its balanced fatty acid composition and antioxidant, antimicrobial, anti-inflammatory, antidiabetic, anticarcinogenic and cardioprotective properties [ 5 , 6 ], and contributes to a more balanced diet, being a fundamental element for those who want to maintain a healthy lifestyle [ 7 ]. It is mostly composed by triacylglycerols (98%), free fatty acids, pigments, phenols, tocopherols, sterols, phospholipids, waxes, squalene, and other hydrocarbons [ 8 ].…”
Section: Introductionmentioning
confidence: 99%